GmARP is Related to the Type III Effector NopAA to Promote Nodulation in Soybean (Glycine max) - Wang, Jinhui; Ma, Chao; Ma, Shengnan; Zheng, Haiyang; Feng, Haojie; Wang, Yue; Wang, Jiangxu; Liu, Chunyan; Xin, Dawei; Chen, Qingshan; Yang, Mingliang (Frontiers in Genetics, 2022)
Type III effectors secreted by rhizobia regulate nodulation in the host plant and are important modulators of symbiosis between rhizobia and soybean (Glycine max), although the underlying mechanisms are poorly understood. Here, we studied the type III effector NopAA in Sinorhizobium fredii HH103, confirming its secretion into the extracellular environment under the action of genistein. The enzyme activity of NopAA was investigated in vitro, using xyloglucan and β-glucan as substrates. NopAA functions were investigated by the generation of a NopAA mutant and the effects of NopAA deficiency on symbiosis were analyzed. Soybean genes associated with NopAA were identified in a recombinant inbred line (RIL) population and their functions were verified. NopAA was confirmed to be a type III effector with glycosyl hydrolase activity, and its mutant did not promote nodulation. Quantitative trait locus (QTL) analysis identified 10 QTLs with one, Glyma.19g074200 (GmARP), found to be associated with NopAA and to positively regulate the establishment of symbiosis. All these results support the hypothesis that type III effectors interact with host proteins to regulate the establishment of symbiosis and suggest the possibility of manipulating the symbiotic soybean–rhizobia interaction to promote efficient nitrogen fixation.